2007
DOI: 10.1111/j.1463-1318.2006.01172.x
|View full text |Cite
|
Sign up to set email alerts
|

Mobile colonoscopic surveillance provides quality care for hereditary nonpolyposis colorectal carcinoma families in South Africa

Abstract: The mobile service provides access to colonoscopy in remote areas without compromising the quality of service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Seven subjects (5%) in the surveillance group and six (12%) in the nonsurveillance group were lost to follow up, so the follow-up rates in the two groups were similar (P = 0.22). During this period, the surveillance group underwent a median of three colonoscopies (range [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven subjects (5%) in the surveillance group and six (12%) in the nonsurveillance group were lost to follow up, so the follow-up rates in the two groups were similar (P = 0.22). During this period, the surveillance group underwent a median of three colonoscopies (range [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…Most mutation carriers live in a remote part of the Northern Cape Province of South Africa, with limited access to health care, and almost no access to endoscopic services. The mobile colonoscopic service offered to these patients has been described previously [5].…”
Section: Introductionmentioning
confidence: 99%
“…Mobile screening vans have been found to be effective instruments in increasing population participation in screening (in and outside the U.S.) for cervical(31), colon(32), breast(33) and lung(34) cancer with no decrement in accuracy, in a cost-effective manner(35). A survey study conducted by us previously suggested that participation in BE screening may increase by the use of mobile screening(15).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important in our setting where we have limited resources available for screening, and most of these families live in areas with little access to health care. We have previously reported the effectiveness of a mobile endoscopy service which has been designed to provide a surveillance colonoscopy service to at-risk individuals in remote areas of the Northern Cape Province of south Africa [4].…”
Section: Introductionmentioning
confidence: 99%